PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI FAKTORISASI SUKU ALJABAR KELAS VIII SMP NEGERI 9 MUARO JAMBI - Apriani Apriani; Buyung Buyung; Relawati Relawati (PHI: Jurnal Pendidikan Matematika, 2017)
This study aims to develop LKS contextualizing algebra-based factorization subjects based on Contextual Teaching and Learning (CTL) for grade VIII SMP students and to know the quality of LKS from the aspect of validity and practicality based on the assessment of material experts, design experts, media experts, student assessment on individual trials , student ratings on small group trials, and student ratings on field trials. Validation is done by 2 material experts, design experts, and media experts. The developed LKS were tested in 3 stages, one to one leaner stage with 3 subjects, small group try-out stage with 6 subjects, and field trials (field try-out) with the subject of 23 students. The result of the research shows that the quality of Student Worksheet (LKS) mathematics of algebra based factorization material based on Contextual Teaching and Learning (CTL) based on the assessment: 1) the material experts obtained the average total of 3.81 included in the "Good" category and if the percentage got 76.2 % are included in the "Very Eligible" category, 2) the design expert obtained an average total of 3.62 which is included in the "Good" category and if the percentage gets 72.4% so it belongs to the category of "Eligible", 3) the media expert gets the 4.43 value included in the "Good" category and if it is punctuated 88.6% to be included in the "Very Eligible" category. Assessment by students is done in 3 stages: 1) individual trials obtained by an average total of 4.75 are included in the "Very Good" category and if the percentage gets 95% so it belongs to the category of "Very Eligible", 2) small group trial is obtained the average total of 4.58 belonging to the category of "Very Good" and if the percentage gets 91.6% so that included in the category of "Very Eligible", 3) field trial obtained an average total of 4.43 which is included in the category of "Very Good" and if censored to 88.6% to be included in the "Very Eligible" category. Thus LKS based mathematics CTL on the materialization factor algebra is declared valid and practical so feasible to be used as a tool of learning mathematics on the materialization of algebraic algebraic.KeyWord: Development, Student Worksheet (LKS), Contextual Teaching and Learning (CTL), ADDIE